A new method for Raman spectral analysis: Decision fusion‐based transfer learning model. (26th December 2022) - Chen, Chen; Ma, Yuhua; Zhu, Min; Yan, Ziwei; Lv, Xiaoyi; Chen, Cheng; Tian, Feng
Abstract: As an emerging technology for artificial intelligence‐aided medical diagnosis, deep learning combined with Raman spectroscopy has great potential. The technology still has some problems in the actual medical diagnosis research process. The differences in spectrometers, experimental conditions, and experimental operations can result in non‐uniform and universally applicable data standards, which in turn lead to low data utilization. At the same time, it is still necessary to retrain the models when building diagnostic models for different diseases, which is time‐consuming and laborious. In this paper, a more complete transfer learning model for multiple types of serum Raman spectra is established for the first time, and a decision fusion strategy is applied to this diagnostic model. The Raman spectral data of serum from hepatitis B patients/control group, serum from abnormal thyroid function patients/control group, and serum from glioma patients/control group were selected as the source domains, and the Raman spectral data of tissue from hepatitis C patients/control group, serum from esophageal cancer patients/control group, and tissue from cervical cancer and cervical inflammation (patients/control) group were selected as the target domains. Three deep neural network models, ResNet, GoogLeNet, and CNN‐LSTM were trained in the source domain data for disease diagnosis, and the trained models were transfer to the target domain. The model is fine‐tuned by freezing different layers and then combined with logistic regression algorithms to construct a decision fusion model, which further improves the model effect. The results show that the proposed method can effectively improve the accuracy of transfer learning models. At the same time, this experiment extends the application of transfer learning in Raman spectroscopy and demonstrates that unrelated and scale‐different Raman datasets are still intrinsically connected, which also lays the foundation for us to build more stable and data‐inclusive spectral transfer learning fusion models in the future. Abstract : In this paper, GoogLeNet, ResNet, and CNN‐LSTM models were trained on the source domain for disease diagnosis. In addition, we added the 1D‐CNN architecture in consideration of a more Raman spectroscopic approach. Then the trained models were transferred to the target domain, and the models were fine‐tuned by freezing layers, and then combined with logistic regression algorithms to construct a decision layer fusion model to further improve the model effect.